PlaySEM - a Platform for Rendering MulSeMedia Compatible with MPEG-V - Saleme, Estêvão Bissoli; Santos, Celso Alberto Saibel (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
MulSeMedia is related to the combination of traditional media (e.g. text, image and video) with other objects that aim to stimulate other human senses, such as mechanoreceptors, chemoreceptors and thermoreceptors. Existing solutions embed the control of actuators in the applications, thus limiting their reutilization in other types of applications or different media players. This work presents PlaySEM, a platform that brings a new approach for simulating and rendering sensory effects that operates independently of any Media Player, and that is compatible with the MPEGV standard, while taking into account reutilization requirement. Regarding this architecture conjectures are tested focusing on the decoupled operation of the renderer.